Strategi Peningkatan Kemandirian Belajar Mahasiswa Pendidikan Bahasa Arab di Era Revolusi Industri 4.0 - Saproni Muhammad Samin; Yenni Yunita; Ismail Akzam (UIR Press, 2021)
This research is qualitative research using a descriptive approach. Data collection techniques in this study using Interview Techniques, Documentation, and Literature Studies. The systematics of strategy formulation refers to five stages. These stages include: (1) Environmental identification (2) Conducting internal and external environmental analysis by measuring strengths and weaknesses as well as opportunities and threats, (3) Formulating key success factors of strategies designed based on the previous analysis, (4) Determining measurable goals and targets, evaluating various alternative strategies by considering the available resources and external conditions faced, (5) Selecting the most appropriate strategy to achieve short-term and long-term goals. This study shows the results of several strategies to increase learning Self-Regulated Learning for Arabic Language Education students at the Universitas Islam Riau as follows; 1) Using a Student-Centered learning (SCL) approach in learning, 2) Using a Net-centric approach in learning media, 3) Building student awareness about Self-Regulated Learning on an ongoing basis, 4) Using E-learning applications that can encourage and stimulate students carry out Self-Regulated Learning, 5) Coordinate between Permanent Lecturers of Study Programs in the formulation of Semester Learning Plans for the core courses of study programs, 6) Create an Arabic language environment, 7) Conduct reward programs for student achievements, 8) There is lecturer guidance for students who will compete. Keywords: Arabic Language Education, Industrial Revolution 4.0, Self-Regulated Learning, Students, Strategy.